Strategic roles of foreign multinational subsidiaries in Malaysia - Zaidah, Mustaffa; Md Zabid, Abdul Rashid; Murali, Sambasivan (2007)
The article presents a study which investigates the strategic roles of foreign multinational subsidiaries in Malaysia. The objective of the study is to explore the different strategic roles of these companies in terms of integration, local responsiveness and technological capabilities of the subsidiaries. Researchers found that these strategic roles were dependent upon the firm and industry characteristics.